Efeitos do laser de baixa intensidade de 100 mW e 50 mW sobre osteoartrite experimental - Alves, Ana Carolina Araruna (2012)
The cartilage damage and destruction are common in osteoarthritis (OA) and are associated with elevated levels of matrix metalloproteinases (MMPs), proteinases that can degrade all components of the extracellular matrix (ECM). The objective was to study the effect of low level laser therapy (LLLT) at 50mW and 100mW in joint damage evaluated by histopathological analysis, and protein expression of metalloproteinases (MMPs) 2 and 9 in the articular lavage. We used 60 male Wistar rats randomly divided into 4 groups of 15 animals each: a control group, an injury group, and two treated groups, one with LLLT 50mW and other with 100mW. The animals underwent OA induction (papain solution 4%) and, on the euthanasia day was collected the articular lavage, which was immediately centrifuged and the supernatant saved for analysis of protein expression by Western blot. The material was stained with hematoxylin and eosin for histopathologic description and Picrosirius Red, to estimate the percentage of collagen fibers. As a result, it was observed that both laser groups were efficient on tissue repair, decreasing the expression of collagen type III and increasing type I at all the experimental times, however, the group LLLT 50mW was better in reducing MMP - 9 in relation to the LLLT 100mW group in 21 days. In conclusion, LLLT 50 mW was more efficient on modulating matrix metalloproteinases and repair of the cartilaginous tissue.